2012
DOI: 10.1111/j.1744-6570.2012.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

A Trickle‐down Model of Abusive Supervision

Abstract: Much of the abusive supervision research has focused on the supervisorsubordinate dyad when examining the effects of abusive supervision on employee outcomes. Using data from a large multisource field study, we extend this research by testing a trickle-down model of abusive supervision across 3 hierarchical levels (i.e., managers, supervisors, and employees). Drawing on social learning theory and social information processing theory, we find general support for the study hypotheses. Specifically, we find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
452
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 447 publications
(476 citation statements)
references
References 77 publications
(114 reference statements)
20
452
0
4
Order By: Relevance
“…They take credit for the efforts of others, blame subordinates for mistakes, discourage informal interaction among subordinates, and deter initiative and dissent" (p. 374). Mawritz, Mayer, Hoobler, Wayne, and Marinova (2012) found that abusive supervision has effects beyond the supervisor-subordinate dyad, which appears according to numerous research efforts to be a common tell-tale of harmful leadership styles. Tepper (2007) provided antecedents of abusive supervision, including organizational injustice, perceived psychological contract breach, and negative affect (p. 1268).…”
Section: Abusive Leadershipmentioning
confidence: 99%
“…They take credit for the efforts of others, blame subordinates for mistakes, discourage informal interaction among subordinates, and deter initiative and dissent" (p. 374). Mawritz, Mayer, Hoobler, Wayne, and Marinova (2012) found that abusive supervision has effects beyond the supervisor-subordinate dyad, which appears according to numerous research efforts to be a common tell-tale of harmful leadership styles. Tepper (2007) provided antecedents of abusive supervision, including organizational injustice, perceived psychological contract breach, and negative affect (p. 1268).…”
Section: Abusive Leadershipmentioning
confidence: 99%
“…Working professionals filled out a survey and had a supervisor fill out another survey. This data collection approach has been successfully used in past research (Grant and Mayer 2009;Mawritz et al 2012;Mayer et al 2012;Morgeson and Humphrey 2006).…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…2 First, people pay more attention to those in high-than low-ranking positions (Fiske, Morling, & Stevens, 1996;Flynn & Amanatullah, 2012;Giordano, 1983;Goode, 1978;Mawritz et al, 2012;Ridgeway & Correll, 2006), which makes high-ranking individuals' behavior a salient signal of descriptive norms. Second, high rank is an explicit indication of the organization's approval and acceptance of an individual, which contributes to the individual's perceived credibility as a role model (Bandura, 1977(Bandura, , 1986Brown et al, 2005;Mayer et al, 2009).…”
Section: Descriptive Norms and Norm Focusmentioning
confidence: 99%
“…This work builds on insights from social learning theory, which emphasizes that people learn how to behave in a given situation by observing others (Bandura, 1977(Bandura, , 1986. Leaders who model bad behavior embolden their subordinates to engage in bad behavior (Brown et al, 2005;Mawritz et al, 2012;Mayer et al, 2010;Mayer et al, 2009). Modeling can also exert an influence up or across the organizational hierarchy as well (e.g., Gino et al, 2009;Robinson & O'Leary-Kelly, 1998;Zey-Ferrell & Ferrell, 1982).…”
Section: Theoretical Backgroundmentioning
confidence: 99%